Combined therapy with ibrutinib and bortezomib followed by ibrutinib maintenance in relapsed or refractory mantle cell lymphoma and high-risk features: a phase 1/2 trial of the European MCL network (SAKK 36/13)Research in context - Urban Novak; Martin Fehr; Sämi Schär; Martin Dreyling; Christian Schmidt; Enrico Derenzini; Thilo Zander; Georg Hess; Ulrich Mey; Simone Ferrero; Nicolas Mach; Carola Boccomini; et al. (EClinicalMedicine, 2023)
Summary: Background: The Bruton's tyrosine kinase inhibitor ibrutinib and the proteasome inhibitor bortezomib have single-agent activity, non-overlapping toxicities, and regulatory approval in mantle cell lymphoma (MCL). In vitro, their combination provides synergistic cytotoxicity. In this investigator-initiated phase 1/2 trial, we established the recommended phase 2 dose of ibrutinib in combination with bortezomib, and assessed its efficacy in patients with relapsed or refractory MCL. Methods: In this phase 1/2 study open in 15 sites in Switzerland, Germany and Italy, patients with relapsed or refractory MCL after ≤2 lines of chemotherapy and both ibrutinib-naïve and bortezomib-naïve received six cycles of ibrutinibb and bortezomib, followed by ibrutinib maintenance. For the phase 1 study, a standard 3 + 3 dose escalation design was used to determine the recommended phase 2 dose of ibrutinib in combination with bortezomib. The primary endpoint in phase 1 was the dose limiting toxicities in cycle 1. The phase 2 study was an open-label, single-arm trial with a Simon's two-stage min–max design, with a primary endpoint of overall response rate (ORR) assessed by CT/MRI. This study was registered with ClinicalTrials.gov, NCT02356458. Findings: Between August 2015 and September 2016, nine patients were treated in the phase 1 study, and 49 patients were treated between November 2016 and March 2020 in the phase 2 of the trial. The ORR was 81.8% (90% CI 71.1, 89.8%, CR(u) 21.8%) which increased with continued ibrutinib (median 10.6 months) to 87.3%, (CR(u) 41.8%). 75.6% of patients had at least one high-risk feature (Ki-67 > 30%, blastoid or pleomorphic variant, p53 overexpression, TP53 mutations and/or deletions). In these patients, ibrutinib and bortezomib were also effective with an ORR of 74%, increasing to 82% during maintenance. With a median follow-up of 25.4 months, the median duration of response was 22.7, and the median PFS was 18.6 months. PFS reached 30.8 and 32.9 months for patients with a CR or Cru, respectively. Interpretation: The combination of ibrutinib and bortezomib shows durable efficacy in patients with relapsed or refractory MCL, also in the presence of high-risk features. Funding: SAKK (Hubacher Fund), Swiss State Secretariat for Education, Research and Innovation, Swiss Cancer Research Foundation, and Janssen.